Analisis Kinerja Keuangan Pemerintahan Daerah Pada Provinsi Kepulauan Bangka Belitung Tahun 2018-2022 - annisa irhamna yusri; Tartila Devy (Politeknik Negeri Padang, 2025)
The implementation of regional autonomy gives authority the regions in managing their own regions. The Bangka Belitung Islands Province is one of the regions resulting from regional expansion after the implementation of regional autonmy. The purpose of this study was to determine the financial performance of local government in the province of The Bangka Belitung Islands in 2018-2022. This research was conducted at the The Bangka Belitung Islands Province BAKUDA which is located on Jl. Belitung Island No. 4 Integrated Office and Settlement Complex. This type of research is descriptive quantitative. The data collection techniques used are documentation, interviews, literature review, and accessing the web and related sites. Local government financial ratios are used as a measuring tool in technical analysis. According to the study’s findings, regional financial independence has remained low over the last five years, from 2018-2022, with an average of 51,21%; the average ratio of local revenue effectiveness is 105,09%; the average ratio of regional financial efficiency is 79,37%; the average ratio of spending harmony indicates that routine spending is allocated more than development spending; the average revenue growth is 5,54%; and the average DSCR is above 2,5%. According to the findings of the analysis of the regional government’s financial performance, it manages the allocated money quite effectively.